2011
DOI: 10.1177/2042018810390259
|View full text |Cite
|
Sign up to set email alerts
|

β3 Receptors: role in cardiometabolic disorders

Abstract: Pharmacological and molecular approaches have shown that an atypical β-adrenoceptor (AR), called β(3)-AR, that is distinct from β(1)-ARs and β(2)-ARs, exists in some tissues in heterogeneous populations such as β(3a)-ARs and β(3b)-ARs. β(3)-ARs belong to a superfamily of receptors linked to guanine nucleotide binding proteins (G proteins). The β(3)-AR gene contains two introns whereas the β(1)-AR and β(2)-AR genes are intronless, leading to splice variants. β(3)-ARs can couple to G(i) and G(s) and they are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…Adrenergic signaling, in particular β3-AR, is a well-established pathway for BAT activation and beige fat development in response to cold temperatures. Common selective β3-AR agonists and antagonists have been summarized in a 2011 review by Bhadada et al (92). Several β3-AR agonists have been shown to induce thermogenesis (93,94).…”
Section: Potential Anti-obesity Drugs and Their Safety Adrenergic Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenergic signaling, in particular β3-AR, is a well-established pathway for BAT activation and beige fat development in response to cold temperatures. Common selective β3-AR agonists and antagonists have been summarized in a 2011 review by Bhadada et al (92). Several β3-AR agonists have been shown to induce thermogenesis (93,94).…”
Section: Potential Anti-obesity Drugs and Their Safety Adrenergic Recmentioning
confidence: 99%
“…Although mirabegron has been found to induce BAT activity as measured by 18 F FDG-PET/CT (99), increase non-esterified fatty acids by up to 68%, and boost resting energy expenditure by up to 5.8% (100) in humans, no β3-AR agonists has been approved to treat metabolic disorders thus far. The most common offtarget binding sites of β3-AR agonists are myocardium and blood vessels (92,(101)(102)(103). Notably, it has been indicated that β3-AR stimulation is related to heart failure because of the negative inotropic effect of β3-AR agonists (104,105).…”
Section: Potential Anti-obesity Drugs and Their Safety Adrenergic Recmentioning
confidence: 99%
“…In contrast, apoptosis as the therapeutic mechanism of action of β-blockers in IH remains unclear [33,68,69]. On the other hand, the capability of β 3 -adrenoceptors (which are expressed in blood vessels, the heart, and adipocytes) [52] to control blood flow at a local level may be another plausible mechanism that requires further research. Certainly, peripheral β 3 -adrenoceptors seem to induce direct and indirect vasodilatation [70], but they produce no clear effects on systemic blood pressure [71].…”
Section: Propranolol As a First-line Treatment For Ihmentioning
confidence: 98%
“…Furthermore, since β 3 -adrenoceptors may be involved in the local control of vasodilatation in some tissues (e.g., at ophthalmic level) [52,70,73], another mechanism of action by which β 3 -adrenoceptor blockers could be useful in therapeutics of IH may be via local vasoconstriction. Of course, further experiments are required to confirm this possibility.…”
Section: Basic Research: Lines Of Evidence Supporting the Potential Cmentioning
confidence: 99%
See 1 more Smart Citation